Caracterização das zonas hidrotermais das Minas Cerrito, Lavras do Sul (RS) - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The Au mines Cerrito do Pires and Cerrito do Rezende are located in Lavras do Sul Intrusive Complex (Neo-proterozóico, 604-590 Ma), placed on the center-west of the Sul-Riograndense Shield. This area is located in the county of Lavras do Sul-RS, at 322 Km to south-west of the estate capital of Rio Grande do Sul, Porto Alegre, and has approximately 1,62 Km² and has Au, Cu and sulfides mineralizations history. These mineralizations are hosted in monzogranitic rocks of shoshonitic geochemistry (monzogranites) and directly associated with sericitic and silicic hydrothermal alteration zones, whose spatial distribution is controlled by fractures, whether or not they are filled by quartz veins. These fractures, in turn, are associated with the Palma Jaques Fault Zone, which controls the circulation of hydrothermal fluids on a regional scale, and has direction approximately parallel to this fault zone. The main objective of this work was to characterize the hydrothermal present in the study area, to identify mineralogical mineralizations and paragenesis, as well as to increase the degree of geological knowledge about these hydrothermal alteration zones and their mineralizations. Thus, the study tools, besides field work, were used as study tools for soundings, transparent slides and X-ray diffraction. With these tools it was possible to identify the altering minerals and clay minerals present. As main results, we can mention that the hydrothermal process in the studied region involves the sodic alteration / albitization of the feldspars, being this alteration overlapped by sericitic and silicic alteration. The main controls observed for the concentration of pyrite were the association between quartz and sericite, abundance of quartz and abundance of billings and / or cavities, which provide the space for the deposition of sulfide, besides acting as a conduit of hydrothermal fluids. Among these, the billing is perhaps the most important control, being that, in some points of areas of sodium change, therefore, where low sulfide is expected to occur, there is a high concentration of Au and sulfides. It is suggested that the Cerrito do Rezende and Cerrito do Pires mines are a porphyry with mineralization associated to the zone of sericitic and silicic alteration, the latter being understood as evolution of the former, to a higher degree.
Keywords: Metassomatismo; Mineralização; Lavras do Sul; Hidrotermalismo; Mina Cerrito; Hidrothermalism; Metassomatism; Mineralization; Cerrito Mine; CNPQ::CIENCIAS EXATAS E DA TERRA